Biological nutrients removal performance under starvation stress: Efficacy deterioration and recovery. (May 2022) - Hou, Baolin; Peng, Sining; Deng, Renjian; Ren, Bozhi; Song, Yujia
Graphical abstract: Highlights: Intensive starvation stress exerted deterioration on TN and TP removal. Invalid P release occurred under intensive starvation stress. Microbial community evolution led to the variation of nutrients removal. Partial recovery of N removal was observed after eliminating starvation stress. The relief of invalid P release accounted for the complete recovery of P removal. Abstract: Biological nutrients removal performance affected by starvation stress was investigated via the addition of pre-anoxic stage to SBR. COD removal efficiency maintained at around 90% regardless of the starvation stress. Starvation stress presented significant impact on nitrogen and phosphorus removal, with noticeable reduction of TN removal and remarkable deterioration of TP removal as prolonging the pre-anoxic time, which was mainly attributed to the integrative effect of carbon source competition, depression of denitrification and invalid P release as well as the variation of microbial community. It was notable that starvation stress exerted distinct evolution on microbial community. The improvement in relative abundance of the certain genera relating to denitrification was the main reason for the partial recovery of nitrogen removal after eliminating stress starvation. The promotion of P uptake capacity accompanied with the relief of invalid P release and the enriched DPAOs accounted for the complete recovery of phosphorus removal.